Nonspecific Nucleoside Triphosphatase P4 of Double-Stranded RNA Bacteriophage φ6 Is Required for Single-Stranded RNA Packaging and Transcription - Pirttimaa, Markus J. (American Society for Microbiology, 2002)
Bacteriophage φ6 has a segmented double-stranded RNA genome. The genomic single-stranded RNA (ssRNA) precursors are packaged into a preformed protein capsid, the polymerase complex, composed of viral proteins P1, P2, P4, and P7. Packaging of the genomic precursors is an energy-dependent process requiring nucleoside triphosphates. Protein P4, a nonspecific nucleoside triphosphatase, has previously been suggested to be the prime candidate for the viral packaging engine, based on its location at the vertices of the viral capsid and its biochemical characteristics. In this study we were able to obtain stable polymerase complex particles that are completely devoid of P4. Such particles were not able to package ssRNA segments and did not display RNA polymerase (either minus- or plus-strand synthesis) activity. Surprisingly, a mutation in P4, S250Q, which reduced the level of P4 in the particles to about 10% of the wild-type level, did not affect RNA packaging activity or change the kinetics of packaging. Moreover, such particles displayed minus-strand synthesis activity. However, no plus-strand synthesis was observed, suggesting that P4 has a role in the plus-strand synthesis reaction also.